Improving the sexual lives of older Australians: Perspectives from a qualitative study - Fileborn, B.; Lyons, A.; Hinchliff, S.; Brown, Graham; Heywood, W.; Dow, B.; Malta, S.; Minichiello, V. (Wiley-Blackwell Publishing Asia, 2017)
Â© 2017 AJA Inc. Objective: To examine older Australian's perspectives on how their sexual lives can best be supported and/or improved. Methods: Fifty-three, semi-structured interviews were conducted with Australian men (n = 30) and women (n = 23) aged 60 and over. Results: Participants identified a range of key issues and areas where their sexual lives could be further supported or improved upon, including normalising the occurrence of sex and sexual desire in later life; increasing and improving on the quality of, cultural representations of older adults; introducing policy, educational and practice-based changes in age care facilities to support the consensual sexual expression of residents; and ensuring that sexual health campaigns and education are inclusive of older people. Conclusion: Our findings present clear implications for further developing sexuality education and public health campaigns, training and education of health-care professionals, and generating social and cultural change pertaining to the acceptability of the diversity of sexual expression in later life.